Potential protective effect of pitavastatin against doxorubicin-induced cardiotoxicity in male rats - Mohammed K. Al-Chlaihawi; Ali M. Janabi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Pitavastatin is a synthetic HMG-CoA reductase inhibitor that differs pharmacologically from other statins in a number of ways because of its cyclopropyl moiety. The expression of lipoprotein lipase is higher at low doses than that of other statins, and cholesterol synthesis is inhibited at lower doses than other statins. These effects include notable long-lasting high-density and apolipoprotein A1-raising activity. Compared to other statins, pitavastatin has the highest bioavailability, about (60%) and the majority of this portion is eliminated unchanged in the bile. following oral administration. Doxorubicin-induced cardiotoxicity or heart failure have a number of potential mechanisms. After doxorubicin administration, cardiac muscle cell injuries are primarily caused by the production of free radicals, increased lipid peroxidation and ROS production in cardiac tissues are the first symptoms of dox-induced cardiotoxicity. Reactive oxygen species are promoted by aglycones and their anthracycline iron complexes. Doxorubicin stimulates both the pathways for extrinsic as well as intrinsic apoptosis. These pathways result in the apoptosis of cells in cardiac muscles due to an imbalance between oxidant and anti-oxidant molecules. Doxorubicin decreased cell viability and stimulated an inflammatory response, as evidenced by an increase in levels of the cytokines interleukin-1 beta, interleukin-6, and tumor necrosis factor-alpha. 28 male rats were divided into four equal groups at random. The rats were allowed to consume water and food in the control group. The rats in the DMSO group were given 10 ml/kg/day of DMSO orally for two weeks. For two weeks, rats in the doxorubicin group (mediated group) gained 2.5 mg/kg of the medication three times per week. Pitavastatin group: Pitavastatin was given orally over the course of two weeks at a rate of 0.64 mg/kg/day. Tumor necrosis factor, interleukin-1β, malondialdehyde, and caspase-3 levels significantly increased (P<0.05), demonstrating that doxorubicin induced cardiotoxicity, as well as a significant decrease in Bcl-2 levels in cardiac tissues and total antioxidant capacity of treated rats when compared to the DMSO and control groups. Pitavastatin significantly reduces the cardiotoxicity brought on by doxorubicin (P< 0.05), as demonstrated by a drop in inflammatory markers like tumor necrosis factor-α and interleukin-1β. The total antioxidant capacity was significantly higher (P< 0.05) in the pitavastatin group versus the doxorubicin-only group, the oxidative marker MDA was also markedly decreased (P< 0.05) in cardiac tissue. Pitavastatin significantly reduced the cardiotoxicity that the chemotherapy drug doxorubicin caused in rats. This was most likely accomplished byinterference with the apoptotic pathway, inflammation, and oxidative stress. This research sought to determine whether pitavastatin might provide protection against the cardiotoxicity that doxorubicin causes by blocking pathways that promote oxidative stress, inflammation, and apoptosis.